Reduction of gastrointestinal protein loss by elemental diet in Crohn's disease of the small bowel. Issue 5 (May 1981) - Logan, R F; Gillon, J; Ferrington, C; Ferguson, A
Abstract : Seven patients with hypoalbuminaemia and extensive jejunoileal Crohn's disease were treated with an elemental diet for 28 to 56 days. Over this time there was an increase in total plasma proteins from mean of 49.1 to 59.0 g/l and a mean rise in serum albumin from 20.7 to 30.0 g/l (P less than 0.05). In addition, there was a 47% mean reduction in plasma protein loss into the gastrointestinal tract and a rise in blood lymphocyte count in all patients (P less than 0.05). These results suggests that, as well as providing nutritional support, elemental diets reduce protein and lymphocyte loss from the diseased intestine.